UPAYA PENINGKATAN PROSES PEMBELAJARAN GURU MATA PELAJARAN MELALUI SUPERVISI KEPENDIDIKAN MODEL BERFIKIR, MENULIS DAN BERDISKUSI DI SDN 14 SIGUNTUR MUDA - Roza, Delisa (Jurnal Manajemen Pendidikan, 2018)
Based on the observations that the researchers did to the teachers at SDN 14 Siguntur Muda, it was found that the teacher's skills in the learning process were still low. The purpose of this study was to improve teacher skills in the Learning Process through Academic Supervision of the Model of Thinking, Writing and Discussing at SDN 14 Siguntur Muda. This research is a school action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 4 Siguntur Muda Elementary School Teachers. Research data was collected using observation sheets. Data is analyzed using percentages. The results showed that the Applicative Education Supervision action to improve the learning process of Model Subjects Thinking, Writing and Discussing increased. This is evidenced by an increase in the ability of teachers in the learning process in class In cycle I to cycle II. The average ability of teachers in the learning process of Thinking, Writing and Discussion Learning models in cycle I was 47.75 in the Less category and in cycle II was 82 in the good category.